A prediction model for nanoparticle diffusion behavior in fibrous materials considering steric and hydrodynamic resistances. Issue 39 (3rd October 2022) - Tian, Di; Qu, Zhiguo; Lai, Tao; Zhu, Guodong
Abstract : Hindered diffusion prediction: a dual-resistance model, which considers steric and hydrodynamic resistances, is proposed and validated by experiments and can be used for accurate and rapid nanoparticle diffusivity prediction in the fibrous medium. Abstract : Precise prediction of the hindered diffusion behavior of electroneutral particles in fibrous media plays a critical role in the development of drugs, polymer membranes, and porous electrodes. However, the random microstructure and unknown coupling relationship of multiple resistance mechanisms lead to the lack of a universal prediction model. In this work, a dual-resistance model is proposed by reconstructed pore-scale simulations, which presents the coexistence of steric and hydrodynamic resistances in the multiplication form. The simulation results show that the relationship between steric resistance and structural parameters (porosity, fiber radius, and particle radius) is exponential, while that for hydrodynamic resistance is polynomial. The dominant diffusion resistance is found to change from hydrodynamic to steric resistance with a decrease in porosity. The fluorescent polystyrene microsphere diffusivity in a series of SiO2 fibrous media is determined by single-particle tracking experiments, quantitatively confirming the dual-resistance model. The present model can be used for rapid diffusivity prediction and fibrous membrane and drug design.